Pengaruh Pendekatan Realistic Mathematics Education (RME) Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas VIII SMP Negeri 31 Padang - MEGA SILVIA (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematical communication skills of students are most important part in achieving to goals of mathematics learning. However, in reality the mathematics communications skills of students are still low. This happens to class VIII of SMPN 31 Padang. The reasons is the learning approach used has not been able to facilititate and develop this abbilities properly. One of the effort made to overcome this is Realistics Mathematics Educations (RME) approach. This type research is a quasi-experimental and descriptive used the design of Static Goup Comparison. Based on the result it was found that mathematical communication skills of student who learn with RME approach are better than conventional lerning.Keywords –  Mathematics Communication Skill, RME, Convensional Learning